To solve for x, we can isolate x on one side of the equation.
First, let's subtract 9 from both sides:
-3x + 9 - 9 = -19 - 9
This simplifies to:
-3x = -28
Next, divide both sides of the equation by -3 to isolate x:
(-3x)/(-3) = (-28)/(-3)
The negative signs cancel out, resulting in:
x = 28/3
So, the value of x is 28/3 or approximately 9.333.
what is the value of x when -3x+9=-19
11 answers
5x-5=50
To find the value of x in the equation 5x - 5 = 50, we can follow these steps:
Step 1: Start with the given equation: 5x - 5 = 50.
Step 2: Add 5 to both sides of the equation to isolate the term with x:
5x - 5 + 5 = 50 + 5
Simplifying both sides gives: 5x = 55.
Step 3: Divide both sides of the equation by 5 in order to solve for x:
(5x) / 5 = 55 / 5
Simplifying gives: x = 11.
Therefore, the value of x that satisfies the equation 5x - 5 = 50 is x = 11.
Step 1: Start with the given equation: 5x - 5 = 50.
Step 2: Add 5 to both sides of the equation to isolate the term with x:
5x - 5 + 5 = 50 + 5
Simplifying both sides gives: 5x = 55.
Step 3: Divide both sides of the equation by 5 in order to solve for x:
(5x) / 5 = 55 / 5
Simplifying gives: x = 11.
Therefore, the value of x that satisfies the equation 5x - 5 = 50 is x = 11.
1/2x -2=3
To find the value of x in the equation 1/2x - 2 = 3, we can follow these steps:
Step 1: Start with the given equation: 1/2x - 2 = 3.
Step 2: Add 2 to both sides of the equation to isolate the term with x:
1/2x - 2 + 2 = 3 + 2
Simplifying both sides gives: 1/2x = 5.
Step 3: Multiply both sides of the equation by 2 to eliminate the fraction:
(1/2x) * 2 = 5 * 2
Simplifying, we get: x = 10.
Therefore, the value of x that satisfies the equation 1/2x - 2 = 3 is x = 10.
Step 1: Start with the given equation: 1/2x - 2 = 3.
Step 2: Add 2 to both sides of the equation to isolate the term with x:
1/2x - 2 + 2 = 3 + 2
Simplifying both sides gives: 1/2x = 5.
Step 3: Multiply both sides of the equation by 2 to eliminate the fraction:
(1/2x) * 2 = 5 * 2
Simplifying, we get: x = 10.
Therefore, the value of x that satisfies the equation 1/2x - 2 = 3 is x = 10.
the sum of 8 and a number divided by 3 equals 6. find the number
To find the number in the equation (8 + x)/3 = 6, we can follow these steps:
Step 1: Start with the given equation: (8 + x)/3 = 6.
Step 2: Multiply both sides of the equation by 3 to eliminate the fraction:
(3) * (8 + x)/3 = 6 * 3
Simplifying gives: 8 + x = 18.
Step 3: Subtract 8 from both sides of the equation to isolate the x term:
8 + x - 8 = 18 - 8
Simplifying gives: x = 10.
Therefore, the number that satisfies the equation (8 + x)/3 = 6 is x = 10.
Step 1: Start with the given equation: (8 + x)/3 = 6.
Step 2: Multiply both sides of the equation by 3 to eliminate the fraction:
(3) * (8 + x)/3 = 6 * 3
Simplifying gives: 8 + x = 18.
Step 3: Subtract 8 from both sides of the equation to isolate the x term:
8 + x - 8 = 18 - 8
Simplifying gives: x = 10.
Therefore, the number that satisfies the equation (8 + x)/3 = 6 is x = 10.
the sum of 8 and a number divided by 3 equals 6. find the number
6
-2/3
-6
52
6
-2/3
-6
52
To find the number that satisfies the equation (8 + x)/3 = 6, we can follow these steps:
Step 1: Start with the given equation: (8 + x)/3 = 6.
Step 2: Multiply both sides of the equation by 3 to eliminate the fraction:
3 * (8 + x)/3 = 6 * 3
Simplifying gives: 8 + x = 18.
Step 3: Subtract 8 from both sides of the equation to isolate the x term:
8 + x - 8 = 18 - 8
Simplifying gives: x = 10.
Therefore, the number that satisfies the equation (8 + x)/3 = 6 is x = 10.
Step 1: Start with the given equation: (8 + x)/3 = 6.
Step 2: Multiply both sides of the equation by 3 to eliminate the fraction:
3 * (8 + x)/3 = 6 * 3
Simplifying gives: 8 + x = 18.
Step 3: Subtract 8 from both sides of the equation to isolate the x term:
8 + x - 8 = 18 - 8
Simplifying gives: x = 10.
Therefore, the number that satisfies the equation (8 + x)/3 = 6 is x = 10.
the sum of 8 and a number divided by 3 equals 6. find the number
A)6
B)-2/3
C)-6
D)52
From the following options which is correct
A)6
B)-2/3
C)-6
D)52
From the following options which is correct
To find the number that satisfies the equation (8 + x)/3 = 6, we can solve for x:
(8 + x)/3 = 6
Multiplying both sides of the equation by 3, we get:
8 + x = 18
Subtracting 8 from both sides, we have:
x = 10
The correct answer is A) 6.
(8 + x)/3 = 6
Multiplying both sides of the equation by 3, we get:
8 + x = 18
Subtracting 8 from both sides, we have:
x = 10
The correct answer is A) 6.